Discriminação e exclusão racial envolvendo estudantes negros: compreensão de professores de colégio público e privado - Azarias, Clodoaldo Reis (2023)
Historically, in Brazil, black people have been excluded from society, being relegated to an inferior class, since the time of slavery, the abolition of slavery, and up to the present day. Racism in Brazil is structured, and brings with it some forms of violence, here we highlight prejudice, exclusion, and discrimination. In the last decades, manifestations and movements have been created with the intention of changing the situation of racism in Brazil, and as a result of these actions related to violence involving black people, it has been sought to implement ways to prevent and combat racial violence in the school environment. The research aims to investigate the perception of teachers regarding racial violence involving black students in the school environment of the State and private Elementary II and Secondary schools in Foz do Iguaçu/PR. Method: a descriptive, exploratory, qualitative study was carried out in public and private schools with Elementary II and High School teachers in Foz do Iguaçu. We used semi-structured interviews and descriptive analysis. Results The interviewed Elementary II and High School teachers from public and private schools in Foz do Iguaçu, PR, understand prejudice, discrimination and exclusion as a reality in school environments. Regarding the existence of racism, the teachers said they had already witnessed discriminatory attitudes such as racial offenses. In relation to the Afro-Brazilian History and Culture curriculum, originated from the Law 10639/2003, the interviewees confirm its use, however, in the teachers' conception, the curriculum is underused, while other didactic materials that portray Afro-Brazilian history and culture are non-existent in the schools of the interviewed teachers. Violence involving blacks is historical and continuous, that is to say, it is a continuous action. Racism is structured and manifests itself throughout society. Some forms of manifestations of racism come as rhetorical; institutional; structural; interpersonal; recreational and cultural. These are behaviors identified in the research and in Brazilian society, and they perpetuate racism, and the school as a social structure is not immune to racist practices and attitudes. The teachers of both public and private institutions agree that there is discrimination and exclusion of black students and recognize the existence of these forms of violence through physical and verbal aggression, and that they find it difficult to understand and deal with the hostility involving black students. We identified differences in the ways schools deal with racism. The public school deals with specific issues, when there are attitudes perceived as racist by the teacher and the issue is solved in the classroom; in the private school, the actions are permanent, through awareness-raising during the school year.